Aquaculture desk reference - Creswell, R. LeRoy (Chapman & Hall, 1993)
This book is a compilation of graphs, tables and charts. Provides Information on water chemistry such a vapor pressure solubility of nitrogen etc. densities and salinities, density in freshwater at different temperatures etc. Converts units of power, geometric formulas, decimal equivalents, units of length, centigrade to Fahrenheit, feet head and water pressure (PSI) etc. Contains enrichment formulations such as "F" enriched seawater, Provasoli's formula, light saturation for microalgae, using a hemacytometer etc. Hatchery information such as; number of eggs per fluid ounce, oxygen consumption, nitrification rates, UV potency, toxicity levels etc. Plumbing specifications, drill and tap sizes, heat transfer, mechanical properties of various building materials etc.